Prisoners of the web. - Wachira Kigotho (Nairobi The Standard Group, 2009)
Students and pupils are getting addicted to the Internet and computer games, but Kenya is among countries with no child protection laws and high unsupervised use by children. Githurai in Nairobi is one of the spots where primary school children browse pornographic sites regularly with the assistance of the cyber cafe operators; Pornography sites are the most commonly visited sites by primary and secondary school students in Nairobi, Lagos and Dar-es-Salaam.
Keywords: Internet Regulation -- Kenya; Internet Regulation -- Kenya; Cyber Laws -- Kenya; Children Protection -- Kenya; Ethics